Neuronal Responses to Water Flow in the Marine Slug Tritonia diomedea - James A. Murray; Jeffry S. Blackwell (Impulse: The Premier Undergraduate Neuroscience Journal, 2005)
The marine slug Tritonia diomedea mustrely on its ability to touch and smell in order to navigate because it is blind. The primaryfactor that influences its crawling direction is the direction of water flow (caused bytides in nature). The sensory cells that detect flow and determine flow directionhave not been identified. The lateral branch of Cerebral Nerve 2 (latCeN2) has beenidentified as the nerve that carries sensory axons to the brain from the flow receptors inthe oral tentacles. Backfilling this nerve to the brain resulted in the labeling of a numberof cells located throughout the brain. Most of the labeled cells are concentrated in the cerebral ganglion where the nerve enters thebrain. The medial and lateral branches of CeN2 were backfilled for comparison of thepattern of cells from each nerve. A map of the cells innervated by latCeN2 reveals thelocation of the stained cells. Extracellular recording from latCeN2 revealed itsinvolvement in the detection of water flow and orientation. The nerve becomes activein response to water flow stimulation. Intracellular recordings of the electricalactivity of these cells in a live animal will be the next step to determine if these cells arethe flow receptors.